2007
DOI: 10.1038/sj.onc.1210597
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of p53 nuclear importation

Abstract: A key step in activation of the p53 tumor suppressor is its transport into the nucleus; however, despite intensive study of p53, the regulation of its subcellular localization is still poorly understood. Here we examined the p53 nuclear importation using a series of mutant cell lines that were resistant to the growth inhibitory effects of temperaturesensitive murine p53 (tsp53). Examination of the p53 subcellular localization in these cell lines showed that the protein was cytoplasmic in most of them. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A search of the literature found only indirect evidence for the role of importin in the transport of most proteins and no direct evidence for a role in the transport of p53 (Kim et al ., 2000; Li et al ., 2007; Liang and Clarke, 1999). We conducted immunoprecipitation experiments to assess the extent of importin association with p53 and its putative role in the nuclear transport of p53.…”
Section: Resultsmentioning
confidence: 99%
“…A search of the literature found only indirect evidence for the role of importin in the transport of most proteins and no direct evidence for a role in the transport of p53 (Kim et al ., 2000; Li et al ., 2007; Liang and Clarke, 1999). We conducted immunoprecipitation experiments to assess the extent of importin association with p53 and its putative role in the nuclear transport of p53.…”
Section: Resultsmentioning
confidence: 99%
“…We examined three cell lines. A1-5 cells are the parental cells from which the ALTR cells were derived (9). ALTR12 cells lack expression of HSF1 and are defective for nuclear importation of p53 (10).…”
Section: Resultsmentioning
confidence: 99%
“…Previously we characterized the nuclear localization of p53 through derivation of a set of cell lines known as ALTR cell lines in which nuclear accumulation of p53 was defective (9). Subsequently we showed that in one of those lines, ALTR12, exclusion of p53 from the nucleus was due to loss of the heat-shock factor 1 (HSF1) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Like nuclear transport factors, many cargos shuttle between the nucleus and the cytoplasm, and their relative distributions can regulate their function (6,10,11). Prominent examples that are subject to this type of localization-mediated regulation are protein kinases and phosphatases, transcriptional regulators, and nuclear transporters for proteins or RNA (6,10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%